PENGARUH PEMBERIAN SIRUP UMBI YAKON TERHADAP KADAR KALSIUM TULANG FEMUR TIKUS PUTIH (Rattus Norvegicus) - Leny Yuanita; Kelvin Rio K (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
The research objectives were to determine: 1) the effect of yacon tuber syrup supplementation on on rat bone calcium levels 2) the correlation of the total amount of short chain fatty acids (ALRP) to the calcium levels of the femur. The experimental animal used was 36 Rattus norvegicus. Were divided into 3 groups of supplement treatment: 1) aquadest, 2) yacon tubers syrup, 3) commercial FOS. After 48 days of treatment, the femur bone was analyzed for calcium levels by the digestion method. The instruments used were HPLC to test ALRP levels, GC to test FOS levels, and AAS to test calcium levels. Data analysis was done through the One Way Anova test (α = 0.05), the Post Hoc LSD, and the product moment correlation. The results of the analysis showed 1) The increase in average calcium levels from the K(-) group to P1 was 1.211 mg/mL and the post hoc statistical test between the K(-) and P1 (p>0.05) groups showed no significant difference between yacon tuber syrup supplementation on calcium levels. mouse bones. 2) Correlation analysis shows the correlation coefficient of r = 0.394 so that there is a low relationship between the total amount of ALRP and calcium levels in the femur bones of experimental animals. Keyword : yacon, FOS, calsium, absorption